HUBUNGAN ANEMIA PADA IBU HAMIL DENGANKEJADIAN PERDARAHAN POST PARTUMPRIMER DI RSUD ROKAN HULU - Wahyuni, Romy (Jurnal Martenity and Neonatal, 2017)
Primary postpartum hemorrhage is bleeding more than 500-600 ml within 24 hours after the birth to go. The WHO said 40% of maternal deaths in developing countries are associated with anemia in pregnancy. In accordance with the description of the Riau provincial health department head, the number of maternal mortality in Riau province is 147 per 100,000 live births. While the incidence of primary postpartum hemorrhage in Rokan Hulu regency based on the data register Melati Rokan Hulu District Hospital in 2011 was 12 cases, in 2012 was about 20 cases in 2013 were about 29 cases and in 2014 was a total of 32 cases. From these data it can be seen that the case of primary postpartum haemorrhage in 2014 there was an increase. This study aims to determine how the relationship between anemia in pregnant women with an incidence of primary postpartum hemorrhage in Rokan Hulu District Hospital in 2014. The research method is analytic survey with cross sectional design. The population in this study all mothers giving birth at hospitals in 2014. The sampling technique sampling saturated with a sample of 143 people from 352 maternal, sample criteria used status of patients who had complete data. Secondary data retrieved from the data register / status of patients in the medical records using the check list sheet. The data analysis of this research is the analysis of univariate and bivariate analysis using chi square test. Results of research on the degree of confidence (CI) 95% acquired anemia with primary postpartum hemorrhage p value = 0.436. The conclusion of this study showed that there was no significant association between anemia in pregnant women with postpartum hemorrhage primary events in hospitals Rokan Hulu 2014. This could have occurred because pregnant women suffer from anemia although there are other factors that lead to postpartum hemorrhage primary among age, parity, chronic energy deficiency (CED) and others.